Faktor – Faktor Yang Mempengaruhi Minat Masyarakat Muslim Membeli Pakaian Thrifting Di Kota samarinda - badawi, Muhammad Iqbal; Tikawati, Tikawati; Hasbi, Muhamad (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The problem that arises is the regulation of Permendag No. 18 of 2020, regarding the prohibition of the sale of used goods, but seeing that there are still many thrifty shops that are open causes people to be interested in buying these items. Fashion trends are now people's lifestyles that continue to stick in everyday life. One of them is thrift fashion which is quite popular among the public, especially teenagers. Thrift fashion is an alternative to exploring appearance, therefore getting used clothing at low prices but still of good quality is in great demand. Thus the purpose of this study was to determine the factors that influence the interest of the Muslim community to buy thrifting/second-hand clothes in Samarinda City. The research method used in this research is quantitative research. The population used was 775,993 muslim people in Samarinda city who were recorded at the Samarinda Central Bureau of Statistics. The sample used was 100 Muslim community respondent data in Samarinda city. The data collection technique used is a questionnaire with a measurement technique using a Likert Scale. The analytical method used is multiple regression analysis. The results of this study indicate that the price and quality factors partially and simultaneously have a significant effect on the interest of the muslim community to buy thrifting/second-hand clothing in Samarinda city.